The place of international obligations in the domestic legal order of states proceedings of the Inaugural Malaysian International Law Symposium - George, Mary; Azmi Sharom; Xavier, Grace; Faizah Nazri; Nurhalida Mohd. Khalil (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2008)
These proceedings discuss the topic, "The Place of International Obligations in the Domestic Legal Order of States" in the context of treaties, Security Council resolutions, international judgments and under general and special rules of international law